Rancang Bangun Aplikasi Toko Bunga Berbasis Web Menggunakan Waterfall dan Pieces - Fikar Wahyu Tyas Tono; Agung Triayudi; Ratih Titi Komala Sari (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2022)
Along with the current development of digitalization technology, almost all aspects have adapted to these changes, including the Indonesian people, who are mostly traders, also take part in this development. The website is one of the digitalization models that is often used in promoting products, both goods and Services, in this case the author takes one example, namely the sale of a flower shop "Bunds Flowers" where in this case the flowers that are sold are not like flowers in general, but there are flowers in the type of paper, plastic, to imported and local flowers, making this flower shop very worthy of having more promotional value, both in terms of conventional (face-to-face) and modern (online/digitalized) sales. This study uses two methods where the waterfall method is applied to the system development process and the PIECES method to analyze the user's response to the system that has been built. In this journal the author aims to build a system where sales and ornamental plant enthusiasts still use traditional media, with the websites help consumers find what they need in an easy way by opening a website. In the analysis process, the respondents have produced several assessments related to the flower shop application, including 1) performance, respondents rated 3.73 (Satisfied) 2) Information, respondents rated 4.33 (Satisfied), 3) Economic, respondents rated 4.33 (Satisfied) , 4) Control and Security, respondents rated 4.10 (Satisfied) and 5 Efficiency, respondents rated 3.73 (Satisfied) and Service, respondents rated 3.73 (satisfied).